Gut bacterial gene changes following pegaspargase treatment in pediatric patients with acute lymphoblastic leukemia. Issue 13 (10th November 2021) - Dunn, Katherine A.; Forbrigger, Zara; Connors, Jessica; Rahman, Mushfiqur; Cohen, Alejandro; Van Limbergen, Johan; Langille, Morgan G. I.; Stadnyk, Andrew W.; Bielawski, Joseph P.; Penny, Susanne L.; MacDonald, Tamara; Kulkarni, Ketan
Abstract: Treatment of pediatric acute lymphoblastic leukemia (ALL) with pegaspargase exploits ALL cells dependency on asparagine. Pegaspargase depletes asparagine, consequentially affecting aspartate, glutamine and glutamate. The gut as a confounding source of these amino acids (AAs) and the role of gut microbiome metabolism of AAs has not been examined. We examined asparagine, aspartate, glutamine and glutamate in stool samples from patients over pegaspargase treatment. Microbial gene-products, which interact with these AAs were identified. Stool asparagine declined significantly, and 31 microbial genes changed over treatment. Changes were complex, and included genes involved in AA metabolism, nutrient sensing, and pathways increased in cancers. While we identified changes in a gene ( iaaA ) with limited asparaginase activity, it lacked significance after correction leaving open other mechanisms for asparagine decline, possibly including loss from gut to blood. Understanding pathways that change AA availability, including by microbes in the gut, could be useful in optimizing pegaspargase therapy.